The short-term impact of COVID-19 on global stock market indices - Gurmeet Singh; Muneer Shaik (Contemporary Economics, 2021)
The COVID-19 pandemic, declared on March 11, 2020 by the World Health Organisation (WHO), has had a severe economic and financial impact on every economy around the world. This paper aims to analyze the short-term impact of COVID-19 on global financial stock market indices. We study the impact of six different WHO announcements regarding COVID-19 on five different sectors (Pharma, Healthcare, Information Technology, Hotel & Airline) based on the indices of three different economies (World, Developed and Emerging economy). We also study the movement of stock prices and volume of nine different global stock market indices (classified as developed & emerging) based on the number of new cases and deaths due to COVID-19. The study's findings suggest that there is a significant effect of COVID-19 on global financial stock markets. However, the effect is varied for developed and emerging economies.
Keywords: G14; G12; G15; 330; COVID-19; Stock Market Index; Sectoral Analysis; Cumulative Abnormal Returns; International Financial Markets